Socioenvironmental determinants as indicators of plague risk in the central highlands of Madagascar: Experience of Ambositra and Tsiroanomandidy districts. - Sitraka Rakotosamimanana; François Taglioni; Masiarivony Ravaoarimanga; Minoarisoa Esther Rajerison; Fanjasoa Rakotomanana (Public Library of Science (PLoS), 2023)
Background Human plague cases are reported annually in the central highland regions of Madagascar, where the disease is endemic. The socioenvironmental characteristics and lifestyles of the populations of the central highland localities could be linked to this endemicity. The aim of this study was to determine socioenvironmental determinants that may be associated with plague risk and explain this variation in epidemiological contexts. Methods The current study was based on the distribution of plague cases between 2006 and 2015 that occurred in localities of districts positioned in the central highlands. Household surveys were performed from June to August 2017 using a questionnaire and direct observations on the socioenvironmental aspects of households in selected localities. Bivariate and multivariate analyses were performed to highlight the socioenvironmental parameters associated with plague risk in both districts. Results A total of 503 households were surveyed, of which 54.9% (276/503) were in Ambositra and 45.1% (227/503) were in Tsiroanomandidy. Multivariate analyses showed that thatched roofs [adjusted odds ratio (AOR): 2.63; 95% confidence interval (95% CI): 1.78-3.88] and ground floor houses [AOR: 2.11; 95% CI: 1.3-3.45-] were significantly associated with the vulnerability of a household to plague risk (p value<0.05). Conclusions Plague risk in two districts of the Malagasy central highlands is associated with human socioenvironmental characteristics. Socioenvironmental characteristics are parameters expressing spatial heterogeneity through the difference in epidemiological expression of the plague in Ambositra and Tsiroanomandidy. These characteristics could be used as indicators of vulnerability to plague risk in plague-endemic areas.